نبی کریم ﷺ کا معلمین سے استفادہ : استشراقی مستدلات کا تاریخی و تنقیدی جائزہ (Al-Aasar, 2025)
This research critically examines the Orientalist hypothesis asserting that the Quranic narratives were derived from the teachings of contemporary Judeo-Christian figures such as Bahira, Nestorius, Waraqa ibn Nawfal, and others. Through a rigorous historical-critical analysis, the study evaluates the validity of these claims by scrutinizing the timing of interactions, the availability of textual sources, and the internal testimony of the Quran. The findings demonstrate significant chronological discrepancies, as many relevant Quranic verses were revealed either prior to these encounters or under circumstances where physical or intellectual borrowing was impossible. Furthermore, the absence of standardized Arabic translations of the Bible in 7th-century Arabia further invalidates the theory of direct textual influence. The study concludes that the Quranic discourse functions not as a product of literary borrowing, but as a divine guardian (Muhaymin) and confirmer (Musaddiq) of the primordial monotheistic message, correcting historical and theological interpolations found in previous sectarian manuscripts.